Parental Oral Violence against Their Teen- ager Children and its Relation with Some Variables: Parental Oral Violence against Their Teen- ager Children and its Relation with Some Variables (Journal of the College of Education for Women, 2019)
AbstractThe Verbal Violence that is directed towards sons is considered one ofthe dehavioural problems that have negative reflections on the personalityof the individual . the increase in the frequency and intensity of thatbehavior in the daily life may lead to psychological and behaviouraldisturbances, and such behaviourhas to be stooped in an early time before itleave negative affects on the personality of the teenager which will not becured or removed easily .The family that is represented by the parents has a prominent effect In theshaping of the teenager's personality , hence forth the normal teenage isa reflection of a stable family life , relatively empty of disturbances andunbalanced styles of dealing with the teenager , the make the teenagerinfected with psychological diseases and with the phenomenon ofaggressive behavior .The verbal malice makes the teenager feel disappointed and its Effectsexceed the limits of his social and ethical behaviours inside hie Family andsociety , it also grows the feelings of inferiority and the Disability to facethe difficulties in life , and it makes him familiar with Negative expression ofhis feelings and the exceeded sensitivity towards Others .This research paper aims at following :- The measurements of the verbal violence that is directed towards Sons .Are there any differences in the use of verbal violence according to -Tybevariable (males / females ) ?- Are there any differences in the use of verbal violence according to Thestudy variable of the father ?- Are there any differences in the use of verbal violence according to Thestudy variable of the mother ?- Are there any differences in the use of verbal violence according to Familyincome?The two researchers have prepared a measure for the verbal violence Whichconsists of (24) items, they have confirmed the validity of the measure,the items have been analyzed statistically on a samble of (400) students(males and females), and the validity of the measure has been alsocalculated by using the two ways of Al-faronbakh for the internal harmonyand the repeating of the test. The researchers have made the final ably onthe research basic sample that consists of (400) student . They have alsoused a number of statistical treatments to answer about the aims of theresearch and its suppositions like: Berson Connection Variable, the Mono-Difference Analysis, Shefeeh Test. One of the most Important results theyhave reached is that the use of veabal violence from the parent towardstheir teenager sons has a poitivw connected relationshib staticallybetween the verbal vioience of the parents on the one hand and between itand the decrease of the family income on the other hand .the two researchers have reached to a number of suggestionsadvices .